2023
DOI: 10.3390/polym15040856
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamic and Dissipative Particle Dynamic Simulation on the Miscibility of NR/CR Blends

Abstract: Natural rubber (NR) exhibits good elasticity, flexural resistance, wear resistance, and excellent mechanical properties, and it has been widely used in aerospace, transportation, medical, and health fields. For NR, however, the resistance to thermal-oxidation and ozone aging is fairly poor. Although aging properties of NR can be significantly improved with the incorporation of chloroprene rubber (CR) according to some references, the miscibility between NR and CR, the morphologies of the binary blends, and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The phase diagram is an important method to study and predict the compatibility of polymer blends 13 . It consists of three main sections: critical point, spinodal curve and binodal curve 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase diagram is an important method to study and predict the compatibility of polymer blends 13 . It consists of three main sections: critical point, spinodal curve and binodal curve 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the minimal size representing the actual size becomes important for calculating thermodynamic parameters 21 . It has been shown that the solubility parameter (δ) and density of polymers stabilize and converge to a constant value with the increasing molecular chain length 13,18,22 . The solubility parameter (δ) and density of NR and BR at different molecular weights need to be calculated to determine the minimum size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 In addition, micromechanics have been applied at the macroscopic scale. 22 Through quantum mechanical (QM) simulation and molecular simulation (specifically, kinetic simulation), microscopic information including the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) values, solubility parameter (δ), mean square displacement (MSD), free volume, etc., [23][24][25] can be calculated to probe into the microstructural properties and mechanisms of the materials. When the predicted results are experimentally verified, the explanation of the mechanism is more reasonable.…”
Section: Introductionmentioning
confidence: 99%